Axial Compression Behaviors of the Steel Tube Confined Reinforced Concrete Columns with Binding Bars. (28th December 2020) - Hu, Hao; Li, Zhengliang; Tu, Xi; Tang, Junfeng
Abstract : An experimental study on the steel tube confined reinforced concrete (STCRC) column with binding bars under axial compression is conducted. The bearing capacity and failure modes are obtained. It can be known that the axial deformation of concrete occurred under compression. The core concrete is wrapped and constrained by the steel tube wall, and the steel tube wall is constrained by binding bars locally, so the local buckling shape of the wall between the binding bars is like wave shape. The 3D finite element model is also developed to analyze the behavior of this type of column under axial compression. Good agreement is shown between the test and predicted results in terms of the load-deformation curves and ultimate strength. The parametric studies indicate that the spacing of binding bars, diameter of longitudinal bars, concrete strength, thickness of the steel tube wall, and section dimension of the column generate different influence on the mechanical properties and bearing capacity. The diameter of longitudinal bars, concrete strength, and section dimension of the column have a great effect on the ultimate bearing capacity. The numerical results also show that the spacing of binding bars has little effect on the ultimate bearing capacity. The larger thickness of the steel tube wall leads to adverse effect on the specimen performance. Finally, the theoretical calculation is carried out, and the result is good.